Energy aspects of the rotary tiller rotor rotation direction in soil tillage - Bajkin Anđelko; Radojčin Milivoj; Ponjičan Ondrej; Radomirović Dragi (Journal on Processing and Energy in Agriculture, 2013)
The aim of this research was to analyze the effects of rotation direction of rotary tiller rotor on the energy expressed as specific work requirement on tractor power take-off (SWPTO). Specific work requirement was measured during field testing. According to the obtained data, the optimal rotor rotation direction was selected based on the working regime and soil condition on the plot. During the operation of rotary tiller with conventional rotor direction, higher specific work requirement was needed for the power of rotary tiller implements through tractor power take-off in comparison to the reverse rotor direction of rotary tiller. The mentioned differences were more noticeable in stubble and soybean fields at lower gears due to the unfavorable physical and mechanical properties of soil and greater presence of vegetation residue. No statistically significant differences were determined on ploughed field. The values of specific work requirement on tractor power take-off (SWPTO) were lower at reverse rotor rotation depending on the change in working speed in comparison to the conventional rotor rotation. Those values on stubble field ranged from 7.0%–23.7%, and on soybean field they ranged from 32.0% to 62.2%. There were no statistically significant differences on ploughed field. The kinematic parameters of rotary tiller, related to the rotation direction, were analyzed in theory and then mathematical expressions were tested on the real values obtained during the field testing. The same trochoides rotated by 180° were observed for both conventional and reverse rotor rotations.